Evaluation of Lipocalin-2 and Vaspin Levels in In Iraqi Women with Type 2 Diabetes Mellitus - Abed, Baydaa Ahmed; Hamid, Ghada Salam (Iraqi Journal of Science, 2022)
The main objective of this study would be that if serum lipocalin-2 and Vaspin levels may be utilized as indicators for chronic in Type 2 diabetes mellitus (T2DM) patients. T2DM treatment is to maintain a healthy glycemic level. If this goal is not met, diabetes consequences, both acute and chronic, may emerge, one of which is obesity. As a result, researchers have investigated the levels of Lipocalin-2 and Vaspin, as well as their connection to obesity and insulin resistance. In this study, we included 60 T2DM (ages 35 to 65 years) and 30 healthy controls. After an overnight fast, blood serum samples were collected, and routine biochemical parameters such as lipocalin-2, Vaspin, and glucose were measured in all samples. At a P <0.05 level, the data were declared significant. Using an ELISA kit, the levels of serum Lipocalin-2 and Vaspin were measured. The results have shown that patients with T2DM had substantially greater blood serum levels of Lipocalin-2 and Vaspin than normal controls (P <0.001 for all comparisons). Also, results revealed Lipocalin-2 and Vaspin have a high positive correlation with each of BMI and Homeostasis Model Assessment for insulin resistance HOMA-IR and moderate positive correlation between Vaspin and Fasting blood glucose.